2008
DOI: 10.1007/s10450-008-9111-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of mercury from single and multicomponent metal systems on activated carbon developed from cherry stones

Abstract: The adsorption of mercury from a single/multisolute aqueous solution by activated carbon (AC) prepared from cherry stones (CS) by chemical activation with H 3 PO 4 , ZnCl 2 or KOH is studied. Three series of AC (i.e., P, H 3 PO 4 ; Z, ZnCl 2 ; K, KOH) were prepared by controlling the impregnation ratio and carbonization temperature. The textural characterization of AC was carried out by gas adsorption, mercury porosimetry and density measurements. The surface chemistry was analyzed by the pH of the point of ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The resulting activated carbons have been used successfully for the removal of metal ions from water streams [17,18].…”
Section: E-mail Address: Teresa@incarcsices (Ta Centeno)mentioning
confidence: 99%
“…The resulting activated carbons have been used successfully for the removal of metal ions from water streams [17,18].…”
Section: E-mail Address: Teresa@incarcsices (Ta Centeno)mentioning
confidence: 99%
“…Other factors than the porous structure could probably influence the adsorption kinetics such as the presence of constrictions in narrow pores or the surface chemistry created in ACFs. In fact, and according to a previous report, the presence of surface groups in samples may render difficult the access of the adsorptive to the adsorption sites because of steric effects (Olivares-Marín et al 2008). This fact is corroborated by the application of molecular modelization to the hydrated HgCl 2 molecule.…”
Section: Adsorption Kineticsmentioning
confidence: 87%
“…Surface basicities of carbons due to π electron of graphene layers and pyrone-type structures on the edges (Montes- Morán et al 1998;Li et al 2002) could have increased with the activation temperature and therefore increased the amount of HgCl 2 adsorbed. In fact, in a previous report (Olivares-Marín et al 2008), the authors suggested that HgCl 2 becomes adsorbed on the surface of the carbons by acid-basic interactions in which HgCl 2 behaves as an acid. That statement was supported by the fact that the amount adsorbed by the carbons fitted well with the contents of basic groups which were strongly dependent on the activation temperature.…”
Section: Adsorption Isothermsmentioning
confidence: 94%
See 1 more Smart Citation
“…Various treatment techniques have been reported and applied for removal of such heavy metals from industrial wastewaters including precipitation (Kurniawan et al 2006;U.S. EPA 1980;Ayres et al 1984), ion-exchange (Chiarle et al 2000;Yang and Renken 2000), membrane processes (Tang et al 2007;Srisuwan and Thongchai 2002;Bessbousse et al 2010), adsorption (Basha et al 2009;Bayramoglu and ArIca 2008;Bhatnagar and Sillanpää 2010;Di Natale et al 2006;Ekinci et al 2002;Olivares-Marin et al 2008;Shafaei et al 2007) etc. Most of these methods suffer from drawbacks like high capital and operational cost and there are also problems in disposal of the residual metal sludge (Namasivayam and Sangeetha 2006).…”
Section: Introductionmentioning
confidence: 98%